The atrial fibrillation ablation pilot study: a European Survey on Methodology and results of catheter ablation for atrial fibrillation conducted by the European Heart Rhythm Association - Arbelo, Elena; Brugada, Josep; Hindricks, Gerhard; Maggioni, Aldo P; Tavazzi, Luigi; Vardas, Panos; Laroche, Cécile; Anselme, Frédéric; Inama, Giuseppe; Jais, Pierre; Kalarus, Zbigniew; Kautzner, Josef; et al. (European heart journal, 2014)
AIMS: The Atrial Fibrillation Ablation Pilot Study is a prospective registry designed to describe the clinical epidemiology of patients undergoing an atrial fibrillation (AFib) ablation, and the diagnostic/therapeutic processes applied across Europe. The aims of the 1-year follow-up were to analyse how centres assess in routine clinical practice the success of the procedure and to evaluate the success rate and long-term safety/complications. METHODS AND RESULTS: Seventy-two centres in 10 European countries were asked to enrol 20 consecutive patients undergoing a first AFib ablation procedure. A web-based case report form captured information on pre-procedural, procedural, and 1-year follow-up data. Between October 2010 and May 2011, 1410 patients were included and 1391 underwent an AFib ablation (98.7%). A total of 1300 patients (93.5%) completed a follow-up control 367 ± 42 days after the procedure. Arrhythmia documentation was done by an electrocardiogram in 76%, Holter-monitoring in 52%, transtelephonic monitoring in 8%, and/or implanted systems in 4.5%. Over 50% became asymptomatic. Twenty-one per cent were re-admitted due to post-ablation arrhythmias. Success without antiarrhythmic drugs was achieved in 40.7% of patients (43.7% in paroxysmal AF; 30.2% in persistent AF; 36.7% in long-lasting persistent AF). A second ablation was required in 18% of the cases and 43.4% were under antiarrhythmic treatment. Thirty-three patients (2.5%) suffered an adverse event, 272 (21%) experienced a left atrial tachycardia, and 4 patients died (1 haemorrhagic stroke, 1 ventricular fibrillation in a patient with ischaemic heart disease, 1 cancer, and 1 of unknown cause). CONCLUSION: The AFib Ablation Pilot Study provided crucial information on the epidemiology, management, and outcomes of catheter ablation of AFib in a real-world setting. The methods used to assess the success of the procedure appeared at least suboptimal. Even in this context, the 12-month success rate appears to be somewhat lower to the one reported clinical trials.
Keywords: Pilot Projects; pooperační péče; recidiva; Catheter ablation; Catheter Ablation; antiarytmika; Atrial fibrillation; znovupřijetí pacienta; Atrial Fibrillation; lidé; Treatment Outcome; Kaplan-Meier Estimate; Patient Readmission; Humans; Registry; Kaplanův-Meierův odhad; Postoperative Care; Electrocardiography; Outcomes; fibrilace síní; pilotní projekty; výsledek terapie; Anti-Arrhythmia Agents; Recurrence; prospektivní studie; Survey; katetrizační ablace; elektrokardiografie; Prospective Studies